Johnny Golightly comes home - Hopkins, Patrick Mark (My University, 2009)
Abstract Johnny Golightly Comes Home is a nonfiction novel about the writing of two books by Pat Hopkins. In particular it is an account of the author’s often troubled interaction with artist John Anthony Boerma, who once took on the persona of Johnny Golightly after reading Truman Capote’s Breakfast at Tiffany’s. It is a story about illusion and fantasy in the creation of a work of conceptual art. As the lies are stripped away, so a new character emerges – that of Johnny Gochristly, the messiah sent to take away the parameters of the world. And in this latter-day passion play the unwitting writer has the role of Judas. The accompanying reflexive essay reviews the themes as they appear in the book – especially those of epiphany brought on by trauma, which leads to a divine mission often associated with extreme eccentricity. It concludes with a section on the writing process.
Keywords: John Anthony Boerma; Johnny Golightly; Epiphany; Trauma; Eccentricity; Outsider; Suicide; Helen Martins; Truth; Nukain Mabusa